Intelligent Interactive Multimedia Systems and Services 2017 - De Pietro, Giuseppe; Gallo, Luigi; Howlett, Robert J.; Jain, Lakhmi C. (Smart Innovation, Systems and Technologies, 2018)
This book constitutes the refereed proceedings of the Tenth International KES Conference on Intelligent Interactive Multimedia Systems and Services: IIMSS-17. It includes 57 full papers organized into topical sections, ranging from visual data processing to big data analytics, and from multimedia to intelligent and cognitive systems. The conference took place as part of the Smart Digital Futures 2017 multi-theme conference, held in Vilamoura, Algarve, Portugal on 21-23 June 2017, which brings together AMSTA, IDT, InHorizons, InMed, SEEL and IIMSS in one venue. It provided an international forum for researchers and scientists to share their work and experiences in the field of multimedia and intelligent interactive systems and services.